JunB: a paradigm for Jun family in immune response and cancer - Ren, Fu-jia; Cai, Xiao-yu; Yao, Yao; Fang, Guo-ying (Frontiers in Cellular and Infection Microbiology, 2023)
Jun B proto-oncogene (JunB) is a crucial member of dimeric activator protein-1 (AP-1) complex, which plays a significant role in various physiological processes, such as placental formation, cardiovascular development, myelopoiesis, angiogenesis, endochondral ossification and epidermis tissue homeostasis. Additionally, it has been reported that JunB has great regulatory functions in innate and adaptive immune responses by regulating the differentiation and cytokine secretion of immune cells including T cells, dendritic cells and macrophages, while also facilitating the effector of neutrophils and natural killer cells. Furthermore, a growing body of studies have shown that JunB is involved in tumorigenesis through regulating cell proliferation, differentiation, senescence and metastasis, particularly affecting the tumor microenvironment through transcriptional promotion or suppression of oncogenes in tumor cells or immune cells. This review summarizes the physiological function of JunB, its immune regulatory function, and its contribution to tumorigenesis, especially focusing on its regulatory mechanisms within tumor-associated immune processes.